ATHLETES’ POSITION WITHIN MONTENEGRIN OLYMPIC MOVEMENT - Begović, Marko (Scientific Journal Management in Sports, 2014)
Th is paper will analyze the institutional position of athletes within the Montenegrin Olympic Movement in order to design better policy mechanisms that will amplify the strengths and dampen the weaknesses. With penetrating to the essence of the formal (informal) organizational structure is intention to improve institutional position of athletes that is likely to lead to better development of sports, to a more fulfi lling career for athletes and their integration as functioning members of the society aft er the end of their careers.